A Structured Approach to Improve Production Process Performance in Operations of Coal Mining Business - Carin, Carin; Sofjan, Keanu Nathaniel; Alden, Alden; Gilbert, Kingsley; Phangestu, Windy; Maheswari, Hesti (Journal of Integrated System, 2025)
In the coal mining industry, operational efficiency and production quality are critical to maintaining competitiveness and meeting growing energy demands. This study focuses on the implementation of quality tools to optimize cycle time within the coal production process, from extraction to final delivery to consumers. The tools utilized include flowchart, check sheet, fishbone diagram, Pareto chart, and control chart. The results showed that they are the most effective tools to solve the cycle time in coal mining industry and improve the quality of final products. A detailed workflow mapping revealed several critical bottlenecks contributing to inefficiencies, such as heavy rain, equipment breakdowns, loading delays, and inadequate interdepartmental coordination. Further root cause analysis using the Fishbone diagram identified key contributors from the environment, machinery, work methods, and management practices. The Pareto chart highlighted that a majority of delays were driven by a few dominant causes, consistent with the 80/20 principle, allowing the company to prioritize impactful improvement actions. The control chart, used to monitor cycle time, indicated the presence of special variations through out-of-control data points. These deviations signify the need for immediate investigation and corrective measures. As a result, the PDCA cycle is recommended as a sustainable improvement framework to address recurring inefficiencies and stabilize production performance. By integrating data-driven decision-making and continuous quality improvement, this study offers a strategic foundation for enhancing productivity and ensuring timely coal distribution, particularly for power generation and industrial sectors. The findings support a structured approach toquality management, contributing significantly to the resilience and sustainability of coal mining operations.